Dampak Digitalisasi Marketing Terhadap Daya Saing UKM Tahu - Novia, Cahyuni; Hasanah, Linda Uswatun; Amalia, Maulida Rizka (Jurnal Pertanian Terpadu, 2022)
SMEs must have competitiveness in marketing strategies so that SMEs can survive in the midst of competition between SMEs. The role of digitization is very important for business owners in determining planning and decision-making strategies that will determine the competitiveness of SMEs. SMEs have difficulty in getting the right marketing digitalization technology solutions because SMEs do not have special staff who are experts in the dynamic field of information technology. Another obstacle is the large variety of technology media products used for marketing digitization. The purpose of this study is to find out how much interaction Small and Medium Enterprises (SMEs) know about digital media and how effective is marketing digitalization on Small and Medium Enterprises (SMEs) based on Media Equation Theory analysis. Next, find out how the impact of digital marketing on sales volume for SMEs tofu in the village of Brani Kulon. This study uses a qualitative method with a Media Equation Theory approach. Researchers use this approach to be able to see the effectiveness of marketing digitalization of Tofu SMEs in the village of Brani Kulon. While the quantitative method used to see the impact of digital marketing on sales volume for SMEs tofu in the village of Brani Kulon